Resposta sorológica e avaliação de proteção fetal em ovinos e bovinos vacinados contra o vírus da diarréia viral bovina (BVDV) - Vogel, Fernanda Silveira Flôres (2000)
The serological response and fetal protection induced by three commercial vaccines against bovine viral diarrhea virus (BVDV) were evaluated in pregnant sheep immunized and subsequently challenged with Brazilian BVDV-1 and BVDV-2 field isolates. Low to moderate antibody titers to BVDV-1 were detected in most animals (45/47) 30 days after the second vaccine administration (geometric mean titers [GMT] of 124.6; 74.6 and 26.8 for vaccines A, B and C, respectively). In contrast, neutralizing activity to BVDV-2 was not detected in several animals (12/47) and was lower in all vaccine groups (GMT 19.1; 14.1 e 15.1). The means titers decreased significantly by day 180 such that several animals had no detectable antibody to BVDV-1 (vaccine B=1/19; C=8/14) and mainly to BVDV-2 (A=7/14; B=13/19; C=13/14). At this time, the ewes were challenged intranasally with either of two Brazilian field isolates of BVDV-1 and BVDV-2. The antibody titers were not sufficient to prevent virus replication, viremia and transplacental transmission such that fetuses from all vaccinated ewes were infected. In a second experiment, calves were immunized three times (days 0, 30 and 180) and tested serologically at different intervals. Neutralizing activity in low to moderate titers to BVDV-1 (25 out of 94 animals) and to BVDV-2 (20/94) were detected at day 60. The GMT and the number of positive animals to BVDV-1 were 109.3 (32/36); 54.6 (22/28) and 25.5 (16/30) for vaccines A, B and C respectively and 19 (27/36); 42.3 (12/28) and 18.4 (10/30) against BVDV-2. At day 180, the GMTs and the number of reagents to BVDV-1 were 28.3 (30/36), 28.3 (20/28) and 16.1 (14/30) and to BVDV-2 were 16.8 (18/36); 21.6 (10/28) and 28.3 (4/30) for vaccines A, B and C, respectively. After the revaccination (day 180), the means titers to BVDV-1 increased significantly in all vaccine groups and to BVDV-2 only in group A. At day 210, the GMT and the number of seropositive animals to BVDV-1 were 104.8 (23/24); 50.3 (24/26) and 43.7 (24/28) and to BVDV-2 were 33.4 (23/24); 23.3 (22/26) and 15.7 (22/28) for vaccines A, B and C. The titers to BVDV-1 were higher than those to BVDV-2 in all three groups. Sera from seropositive animals from the three vaccine groups were tested against four Brazilian isolates of BVDV-1 and two of BVDV-2. In addition to the low to moderate titers, the cross-neutralization assays revealed dramatic differences in neutralizing activity when a given serum was tested against different viruses. These results demonstrate that the vaccines induced low to moderate titers to BVDV-1 and even lower titers to BVDV-2. The magnitude of serological response was highly variable among animals and several animals did not respond to vaccination. In sheep, the antibody levels induced by vaccination were not sufficient to protect the fetuses upon challenge. These results also indicate the suitability of sheep as a model to test the efficacy of BVDV vaccines.